2018
DOI: 10.1097/jpo.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of a Video Analysis System (PnO Clinical Movement Data) and the Universal Goniometer in the Measurement of Hip, Knee, and Ankle Sagittal Plane Motion among Healthy Subjects

Abstract: Throughout the rehabilitation process, measuring joint range of motion (ROM) is essential to understand joint kinematics. The universal goniometer (UG) is the most common tool used in the clinical setting for joint ROM measurement. However, a review of the literature examining the reliability of the UG has demonstrated considerable variation in results and highlighted the necessity of introducing a more reliable tool. This study aimed to investigate the reliability of a 2-dimensional video analysis system, PnO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Manual measures also include inherent variation and error, which could be caused by inexact placement of a goniometer or tape measure. 18 For joint angle measures, Reissner et al 19 have shown that this error can be up to 7°with respect to the actual angle. It should be noted that computer vision and clinician estimates were taken from separate trials, so intertrial variability (and clinician error) may have affected our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manual measures also include inherent variation and error, which could be caused by inexact placement of a goniometer or tape measure. 18 For joint angle measures, Reissner et al 19 have shown that this error can be up to 7°with respect to the actual angle. It should be noted that computer vision and clinician estimates were taken from separate trials, so intertrial variability (and clinician error) may have affected our results.…”
Section: Discussionmentioning
confidence: 99%
“…Manual measures also include inherent variation and error, which could be caused by inexact placement of a goniometer or tape measure. 18 For joint angle measures, Reissner et al . 19 have shown that this error can be up to 7° with respect to the actual angle.…”
Section: Discussionmentioning
confidence: 99%
“…18 Some variation in a goniometric joint angle measurement can emerge, if the physiotherapist has improper placement of its fulcrum over the centre of rotation of the joint or wrong anatomic structures. 19 Melián-Ortiz et al 20 have shown, that the variation can be 1° to 7° from the actual degree in manual joint measurements with a universal goniometer. To minimize the variation, physiotherapists should follow standard written principals.…”
Section: The Requirements On Computer Vision-based Motion Analysis From a Physiotherapist Point Of Viewmentioning
confidence: 96%